2019
DOI: 10.1016/j.dcn.2019.100616
|View full text |Cite
|
Sign up to set email alerts
|

Focused attention predicts visual working memory performance in 13-month-old infants: A pupillometric study

Abstract: Attention turns looking, into seeing. Yet, little developmental research has examined the interface of attention and visual working memory (VWM), where what is seen is maintained for use in ongoing visual tasks. Using the task-evoked pupil response – a sensitive, real-time, involuntary measure of focused attention that has been shown to correlate with VWM performance in adults and older children – we examined the relationship between focused attention and VWM in 13-month-olds. We used a Delayed Match Retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 91 publications
2
30
0
Order By: Relevance
“…It seems likely that the type of attention assessed is important here – the study by Holmboe, Bonneville-Roussy, et al (2018) used primarily measures of saccadic reaction time (see, Geeraerts et al, 2019, for a similar negative finding with a saccadic reaction time measure in older infants), whereas Blankenship et al (2019) focused on peak look duration and shift rate to and from a video. Another recent study by Cheng, Kaldy, and Blaser (2019) found that focused attention, as assessed by pupil response during stimulus encoding, directly predicted subsequent WM performance in 13 month olds. Finally, research in toddlers by Veer, Luyten, Mulder, van Tuijl, and Sleegers (2017) indicated that selective attention at 2½ years was predictive of WM and response inhibition at 3 years.…”
Section: The Development and Neural Substrates Of Ef Componentsmentioning
confidence: 96%
“…It seems likely that the type of attention assessed is important here – the study by Holmboe, Bonneville-Roussy, et al (2018) used primarily measures of saccadic reaction time (see, Geeraerts et al, 2019, for a similar negative finding with a saccadic reaction time measure in older infants), whereas Blankenship et al (2019) focused on peak look duration and shift rate to and from a video. Another recent study by Cheng, Kaldy, and Blaser (2019) found that focused attention, as assessed by pupil response during stimulus encoding, directly predicted subsequent WM performance in 13 month olds. Finally, research in toddlers by Veer, Luyten, Mulder, van Tuijl, and Sleegers (2017) indicated that selective attention at 2½ years was predictive of WM and response inhibition at 3 years.…”
Section: The Development and Neural Substrates Of Ef Componentsmentioning
confidence: 96%
“…Our work established that just as in adults (Unsworth & Robison, 2017), moment-to-moment fluctuations in cognitive effort modulate infants' working memory performance. For instance, in a group of 13-month-old infants from a recent study of ours (Cheng et al, 2019a), the highest quartile of participants-based on their average pupil dilation during the presentation of to-be-remembered stimuli-achieved 66% correct, and the lowest quartile performed at chance.…”
Section: Effort Modulates Memorymentioning
confidence: 92%
“…In addition, Sonne, Kingo, and Krøjgaard (2017) found a positive correlation between pupil dilation and memory retrieval in an imitation task in 20-month-old toddlers over a 2-week period. Until the work of our group (Cheng, Kaldy, & Blaser, 2019a), the relationship between effort (as measured by the pupil response) and working memory had been studied only in school-age children (7 years and up) who can reliably follow verbal instructions (E. L. Johnson, Miller Singley, Peckham, Johnson, & Bunge, 2014; Karatekin, Couperus, & Marcus, 2004).…”
Section: Effort Modulates Memorymentioning
confidence: 99%
See 2 more Smart Citations